Distribution of vascular plants in Mongolia − I Part - Shukherdorj Baasanmunkh; Batlai Oyuntsetseg; Zagarjav Tsegmed; Khurelpurev Oyundelger; Magsar Urgamal; Batdelger Gantuya; Chuluunbat Javzandolgor; Nyamjantsan Nyambayar; Petr Kosachev; Hyeok Jae Choi (Mongolian Journal of Biological Sciences)
In the present article, we provided grid distribution maps of vascular plants in Mongolia based on a 40 x 40 km2 grid cell size. We selected 40 native vascular plant species, belonging to 31 genera and 17 families. With the exception of a few species, the majority of species are distributed in Asian countries, including the Asian parts of Russia. Moreover, given species are collected as herbarium specimens and photographed in their natural habitats during our field surveys. The global and regional distribution, natural habitat, and conservation status of each species are provided in detail.